Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.2147/rrcc.s38614
|View full text |Cite
|
Sign up to set email alerts
|

SERCA2a: its role in the development of heart failure and as a potential therapeutic target

Abstract: Abstract:The complexity of heart physiology has delayed the implementation of efficient, feasible, and safe therapies to fight against heart diseases for many years. As knowledge of the precise mechanisms governing cardiac hypertrophy and heart failure development increases, the availability of new therapeutic alternatives also grows. Since the cardiomyocyte physiology deeply depends on the correct calcium handling, many efforts to describe accurately the excitation-contraction coupling process in the heart an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 129 publications
0
2
0
Order By: Relevance
“…The lower cardiac contractility indexes (LVDP, RPP, and ± dP/dt), could be illustrated through reduced SERCA2a expression. 45 Further, GA increased the low expression of SERCA2a induced by I/R injury in the heart tissue. These results indicated that GA could improve cardiac performance by enhancing SERCA2a gene expression in hypertrophic hearts induced by ISO in I/R injury conditions for the first time.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…The lower cardiac contractility indexes (LVDP, RPP, and ± dP/dt), could be illustrated through reduced SERCA2a expression. 45 Further, GA increased the low expression of SERCA2a induced by I/R injury in the heart tissue. These results indicated that GA could improve cardiac performance by enhancing SERCA2a gene expression in hypertrophic hearts induced by ISO in I/R injury conditions for the first time.…”
Section: Discussionmentioning
confidence: 96%
“…LDH and CK-MB levels in the serum were significantly enhanced in the ISO injected rats compared with the control rats (7726. 45…”
Section: Impacts Of Ga On Ldh and Ck-mb Valuesmentioning
confidence: 99%